Quiet Noise: Adult Education’s Silence on Disabilities - Carol Rogers-Shaw (Adult Education Research Conference, 2017)
This literature review documents the omission of disability in adult education discourse on power distribution, access to education, and inclusion in educational settings and suggests ways to address this exclusion.
Keywords: disability; power; inclusion; adult education discourse; literature review